DYNAMICS OF BIOSTATISTICS LEARNING: CHALLENGES AND OPPORTUNITIES TO IMPROVE TEACHING EFFECTIVENESS FOR NURSING STUDENTS - Yuyun Tafwidhah; Mita Mita; Muhammad Ali Maulana; Yoga Pramana; Hanafi Hanafi; Muhammad Agung Krisdianto (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Biostatistics is an important subject in nursing education because it contributes to clinical decision-making and health research. However, many nursing students find biostatistics difficult because they are not directly used in nursing practice. This study aims to explore the dynamics of biostatistical learning to improve teaching approaches in the future. The study uses a Mixed Methods Research (MMR) design with an explanatory sequential approach which is carried out in two stages. The first stage involved 94 nursing students to measure satisfaction and concentration in learning. Quantitative results revealed that 80.9% of students were satisfied, although dissatisfaction arose from unclear goals and inappropriate lecture times. In addition, 72.3% of students had moderate concentration, with peer conversation invitations being the main challenge. In the second stage, a Focus Group Discussion (FGD) with 8 students explored these findings further. The integration of qualitative and quantitative data identifies key themes, namely clarity of learning objectives, lecture time, classroom atmosphere, technology support, and teaching effectiveness. These findings emphasize the need for better teaching strategies and time management to improve student satisfaction, focus, and understanding of biostatistics. Addressing this dimension will increase the effectiveness of biostatistics education for nursing students.